THE INFLUENCE OF DRILL BALL AND FOOTWORK TRAINING ON JUMPING SMASH BADMINTON ACCEPTANCE AT PB FORZA JUNIOR PURWODADI 2020 - Joko Sulistiyono; Teguh Santosa; Amin Mulyanto, (Journal Of Indonesia Sport Education and Adapted Physical Education (JISEAPE), 2022)
This study aims to determine the effect of the ball drill and footwork method on the acceptance of the Jumping Smash athlete PB Forza Junior Purwodadi Grobogan. This study used the Two Groups Pre-test-post-test Desing design. The population in this study were 25 athletes, PB Forza Junior Purwodadi. The sampling technique used purposive sampling, with the following criteria: (1) the attendance list was at least 75% (activeness following the training), (2) the players were PB badminton athletes. Forza Junior Purwodadi, (3) the minimum length of exercise is 6 months. (4) This study was carried out under the Covid 19 health protocol, where the maximum limit of people in a building is at least 20 people. Based on these criteria, 14 athletes were fulfilled. And research is carried out in different places to comply with these health protocols. The results show that (1) The results of the analysis show that there is an increase in the acceptance of the Jumping Smash athlete PB Forza Junior Purwodadi before and after the Drilling smash training method exercise. This is indicated by the value of t count = 10.331> t table 2.17, and a significance value of 0.000 <0.05, with a percentage increase of 83%. (2) The influence of the Footwork training method on athletes PB Forza Junior Purwodadi acceptance of Jumping Smash with that t count 12.021 and t table 2.17 (df 12)) with a significance value of p of 0.000. Therefore t count 12.021> t table 2.44, and a significance value of 0.000 <0.05, with a percentage increase of 43%.(3) The ball drill method is more effective in the acceptance of Jumping Smash athletes PB Forza Junior Purwodadi than the Footwork training method, with the difference in the average postest is 1.143.